Measurement of motivational imagery abilities in sport - Gregg, M.; Hall, C. (Journal of Sports Sciences, 2006)
Athletes report using imagery most often to successfully cope with and master challenging situations. This function of imagery is termed "motivational general-mastery" and includes imagining being focused, confident and in control in difficult circumstances. Also, athletes often use imagery to regulate their arousal levels (e.g. relaxing, psyching up) and this function of imagery is termed "motivational-general arousal". While most athletes report employing these two motivational functions of imagery, their ability to do so has not been examined. The aim of the present study was to develop a measure of motivational general sport imagery ability, the Motivational Imagery Ability Measure for Sport (MIAMS). This was accomplished through three phases. Across these phases, evidence was generated showing that the psychometric properties of the instrument are adequate. In addition, the relationship of scores on the MIAMS to demographic variables, including sex, sport type and competitive standard, were examined. It was found that athletes participating at a competitive level scored higher on the MIAMS than athletes participating at a recreational level.